PHYSIOTHERAPY MANAGEMENT IN POST OPERATION CABG (CORONARY ARTERY BYPASS GRAFT): A CASE STUDY - Nabilah, Amiratun; Wijianto, W; Purbasasana, P (Academic Physiotherapy Conference Proceeding, 2021)
Introduction : Coronary Artery Bypass Graft (CABG) is a surgical procedure to restore normal blood flow to the heart by bypassing blocked coronary arteries. The purpose of this study was to determine the effectiveness of giving Deep Breathing Exercise in cases of postoperative CABG (Coronary Artery Bypass Graft). Case Presentation: A 55 year old man with a dentist job. The patient complains of pain in the chest that was incised, pain occurs when sneezing or coughing. Management and Outcome : The patient is given deep breathing exercise. Do repetitions for 1 minute with a break of 2 seconds for each repetition, done 2 times a day. Pain was measured using the NPRS (Numeric Pain Rating Scale). Discussion : After being given therapy, it was found that there was a decrease in motion pain as much as 2 points which was measured using NRS where the values at T(beginning):5 and T(end) were:3. Conclusion : Giving therapy in the form of deep breathing exercise modality can reduce chest pain (incise scar) in patients after CABG (Coronary Artery Bypass Graft) surgery.